Four‐dimensional ultrasound biometry following botulinum toxin type A injection to the pelvic floor. Issue 1 (17th November 2021) - Nesbitt‐Hawes, Erin M.; Dietz, Hans Peter; Ledger, William L.; Abbott, Jason A.
Abstract: Aims: The objective of this study was to provide follow‐up data on four‐dimensional ultrasound (4DUS) morphometry for women having botulinum toxin type A (BoNT‐A) treatment of pelvic floor tension myalgia (PFTM). Materials and Methods: A prospective cohort study was performed from October 2013 to June 2018, recruiting women scheduled for BoNT‐A injection in the pelvic floor musculature. Translabial 4DUS, vaginal pressure assessment by manometry and pain visual analog scales (VAS) were performed on all women before injection and again at 4, 12, and 26 weeks. The BoNT‐A injection was performed under 4DUS guidance. Results: Twenty‐nine women had 44 injections over the course of the study. Although improvements were seen in VAS scores for dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia, there were no significant differences in ultrasound biometry at either rest, Valsalva, or on contraction when comparing postinjection measurements at 4, 12, and 26 weeks with pre‐injection baseline. Similarly, vaginal pressure readings at rest demonstrated a significant improvement throughout the 4, 12, and 26 week follow‐up, with a reduction in maximal contraction at 4 and 12 but not 26 weeks. Conclusions: This study demonstrates that 4DUS biometry of the pelvic floor does not correlate with clinical pain and vaginal pressure outcomes for BoNT‐A injection in the context of PFTM.